Irradiated Pollen-Induced Parthenogenesis for Doubled Haploid Production in Sunflowers (Helianthus spp.) - Hongxia Wang; Hongyan Hou; Chao-Chien Jan; Wun S. Chao (Plants, 2023)
Doubled haploid (DH) technology is a tool used to develop large numbers of inbred lines and increase the rate of genetic gain by shortening the breeding cycles. However, previous attempts to produce DH sunflower plants (Helianthus spp.) have resulted in limited success. In this research, we applied gamma-induced parthenogenesis to assist the production of DH sunflowers. The objectives of the study included (1) identifying optimal gamma ray doses for inducing DH sunflowers using two cytoplasmic male sterility (CMS) lines as female plants and two male pollinators with recognizable morphological markers, (2) selecting new male pollinators from wild sunflower varieties, and (3) testing the efficacy of the selected male pollinators using emasculated non-male sterile sunflower lines as female plants. In these experiments, pollen grains were irradiated with gamma ray doses ranging from 50 to 200 Gy. The optimal gamma ray dose for pollen grain irradiation and DH plant production was identified to be 100 Gy. In addition, a cultivated (G11/1440) and a wild-type (ANN1811) sunflower line can be used as common male pollinators for their distinctive morphological markers and wide capacity for DH induction by gamma-irradiated pollen grains.